Superior vena cava syndrome associated with Nocardia farcinica infection. Issue 5 (May 1997) - Abdelkafi, S; Dubail, D; Bosschaerts, T; Brunet, A; Van Camp, G; de Marneffe, M; De Vaster, J M; Ninane, V
Abstract : A case is described of severe Nocardia farcinica infection which mimicked a pulmonary neoplasm with pneumonia, superior vena cava syndrome, pericarditis, and hypertrophic osteoarthropathy. Treatment with trimethoprim-sulphamethoxazole and surgery resulted in complete recovery.